Cybercrime: key issues and debates - Gillespie, Alisdair A. (Routledge, Taylor & Francis Group, 2026)
Now in its third edition, "Cybercrime: Key Issues and Debates" provides a valuable overview of this fast-paced and growing area of law. As technology develops and internet-enabled devices become ever more prevalent, new opportunities exist for that technology to be exploited by criminals. One result of this is that cybercrime is increasingly recognised as a distinct branch of criminal law. The book offers readers a thematic and critical overview of cybercrime, introducing the key principles and clearly showing the connections between topics as well as highlighting areas subject to debate. Written with an emphasis on the law in the UK but considering in detail the Council of Europe's important Convention on Cybercrime, this text also covers the jurisdictional aspects of cybercrime in international law. Themes discussed include crimes against computers, property, offensive content, bullying, sexual offences, and cybercrime investigation. This new edition has been brought up to date to include coverage of the latest developments in this fast-moving area, including AI and end-to-end encryption. New chapters dedicated to cyberbullying and cyberstalking and online sexual abuse have also been incorporated. Clear, concise and critical, this book is designed for students studying cybercrime for the first time, enabling them to get to grips with an area of rapid change